2021
DOI: 10.1007/s11625-021-01053-3
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and learning for change: analysis of a post-graduate One Health program

Abstract: As problematized through the One Health concept, global health issues are defeating conventional disciplinary approaches since they unfold across various scientific domains and across all levels of society. Calling for a change in the way knowledge is generated and used to tackle these complex societal issues, the One Health concept appears as a particular perspective within sustainability science. Various academic initiatives, inspired by the One Health concept, are emerging to prepare future health practitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…This body of data indicates that while there is considerable disparity between all the 43 programmes analysed, there still exists a significant uniformity. An additional highlight from the data generated is that the majority of OH programmes are often designed around the strengths of the organising academic institutions, which was also previously noted by Sidikou et al, [26]. Based on this current study, it was observed that each OH programme gives a bird's eye view of the OH concept, but despite this, each still emphasises particular subsets of OH.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This body of data indicates that while there is considerable disparity between all the 43 programmes analysed, there still exists a significant uniformity. An additional highlight from the data generated is that the majority of OH programmes are often designed around the strengths of the organising academic institutions, which was also previously noted by Sidikou et al, [26]. Based on this current study, it was observed that each OH programme gives a bird's eye view of the OH concept, but despite this, each still emphasises particular subsets of OH.…”
Section: Discussionsupporting
confidence: 74%
“…would be more suited. This underscores the need for additional studies of OH programmes using a pedagogical approach, similar to Amuguni et al [ 35 ] and Sidikou et al [ 26 ], to determine how OH core competencies are incorporated. Results from these studies could serve as guides for subsequent OHHLEP recommendations.…”
Section: Discussionmentioning
confidence: 94%
“…Within a rapidly changing global environment, the need for practitioners and scientists trained and competent in integrative approaches to health has increased substantially. One Health practitioners are suitably positioned to act as agents of change in this domain (Sidikou et al, 2021). Therefore, NEOH proposes updated One Health core competencies to reflect the evolving narratives in One Health, from the former anthropocentric view of disease avoidance at the human-animal-environment interface, to a more holistic approach that strives to sustainably balance the health of people, animals, plants and ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…In all cases, acquiring OH competencies is a social process, calling for mutual and shared learning. These questions or even blurs the border between learning and teaching, with all participants of a program intervening in the process as equals (Sidikou et al, 2021).…”
Section: Limitationsmentioning
confidence: 99%
“…11 Examples of such contexts include team-based learning, flipped classrooms, and problem-based learning, which facilitate constructive dialogue, exchange of ideas and opinions, and a broadening of understanding of complex problems. 12 These contexts provide an ideal environment for fostering systems thinking skills, leading to better, more sustainable solutions. For instance, problem-based learning employs a selfdirected learning (SDL) model that emphasizes student groups taking ownership of their own learning as a team while working collaboratively under the guidance of a facilitator.…”
Section: Participative Learning Contextsmentioning
confidence: 99%